Carotid flow rates and flow division at the bifurcation in healthy volunteers. - Marshall, I; Papathanasopoulou, P; Wartolowska, K (2004)
In nine healthy subjects, magnetic resonance imaging was used to measure blood flow waveforms in the common (CCA), internal (ICA) and external (ECA) carotid arteries. Useful data were acquired from 14 carotid arteries in total. Flow rates were determined from regions of interest placed over the arteries in CINE-phase contrast velocity encoded images. Use of a normalized cardiac cycle allowed the combination of flow waveforms from individuals. Time-averaged group mean flow rates were 6.16, 4.14 and 1.59 ml s(-1) for the CCA, ICA and ECA, respectively. Time-averaged values for the flow division ratios ICA/CCA, ECA/ICA and ECA/CCA were 0.70, 0.39 and 0.26, respectively. The data will be of use in future physiological studies and in computational modelling of carotid artery haemodynamics.